Correction: Hussain et al. An Epidemiological Survey Regarding Ticks and Tick-Borne Diseases among Livestock Owners in Punjab, Pakistan: A One Health Context. Pathogens 2021, 10, 361 - Sabir Hussain; Abrar Hussain; Jeffery Ho; Jun Li; David George; Abdul Rehman; Jehan Zeb; Olivier Sparagano (Pathogens)
There was an error in the original publication [...]